THE LEVEL OF PHYSICAL FITNESS OF THE RUNNERS OF THE ATHLETICS DEPARTMENT AT BOSM - Munisa R. Ulugbekova (Oriental Journal of Education, 2023)
This article discusses and analyzes the topic of the level of physical fitness of the runners of the track and field department at BOSM.